Sex differences in patterns of referral and resource utilization in the cardiology clinic: an outpatient analysis - Vicent, Lourdes; Rosillo, Nicolás; Moreno, Guillermo; Salguero-Bodes, Rafael; Goñi, Clara; Bernal, José Luis; Seara, Germán; Bueno, Héctor (Frontiers in Cardiovascular Medicine, 2023)
Aims Women may have different management patterns than men in specialised care. Our aim was to assess potential sex differences in referral, management and outcomes of patients attending outpatient cardiac consultations. Methods and results Retrospective observational analysis of patients ≥18 years referred for the first time from primary care to a tertiary hospital cardiology clinic in 2017–2018, comparing reasons for referral, decisions and post-visit outcomes by sex. A total of 5,974 patients, 2,452 (41.0%) men aged 59.2 ± 18.6 years and 3,522 (59.0%) women aged 64.5 ± 17.9 years (P < 0.001) were referred for a first cardiology consultation. The age-related referral rates were higher in women. The most common reasons for consultation were palpitations in women (n = 676; 19.2%) and ECG abnormalities in men (n = 570; 23.2%). Delays to cardiology visits and additional tests were similar. During 24 months of follow-up, women had fewer cardiology hospitalisations (204; 5.8% vs. 229; 9.3%; P = 0.003) and lower mortality (65; 1.8% vs. 66; 2.7%; P = 0.028), but those aged <65 years had more emergency department visits (756; 48.5% vs. 560; 39.9%, P < 0.001) than men. Conclusion There are substantial sex differences in primary care cardiology referral patterns, including causes, rates, decisions and outcomes, which are only partially explained by age differences. Further research is needed to understand the reasons for these differences.